1988
DOI: 10.1111/j.1365-2230.1988.tb00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic abnormalities in dyskeratosis congenita-report of five cases

Abstract: Summary Five patients with dyskeratosis congenita arc described. The cytogenetic studies showed varying frequencies of chromosomal abnormalities which included gaps, chromatid breaks and pulverizations, ranging from 4 to 22%. These findings suggest that chromosomal breakage may be of fundamental importance in the etiology of dyskeratosis congenita and it could represent a genetic marker for the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

1989
1989
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…Hair is involved in 16 % of patients , as premature hair greying , , or loss , , , , of scalp hair or eyebrows. Sparse body hair has also been reported , .…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Hair is involved in 16 % of patients , as premature hair greying , , or loss , , , , of scalp hair or eyebrows. Sparse body hair has also been reported , .…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Several studies have reported on the cytogenetic findings in DC cells. Spontaneous chromosomal breaks in DC lymphocytes have been reported in some studies (Scoggins et al, 1971;Morrison, 1974;Aguilar-Martinez et al, 1988), but not in others (Inoue et al, 1973;Schroeder & Hofbauer, 1974;Sirinavin & Trowbridge, 1975;Gutman et al, 1978;Connor & Teague, 1981;Womer et al, 1983;Pai et al, 1989). Excessive spontaneous (Burgdorf et al, 1977) and clastogen-induced (Carter et al, 1979) sister chromatid exchange (SCE) have also been reported in DC lymphocytes.…”
Section: Dyskeratosis Congenita Is a Chromosomal Instability Disordermentioning
confidence: 99%
“…In their letter on chromosome abnormalities in dyskeratosis congenita (DKC), Scappaticci et al [19891 reported on the occurrence of chromosome rearrangements and of an increased rate of chromosome breakage in cultures of fibroblast-like cells derived from unspecified lesions of a DKC patient. Meanwhile, about 20 publications have reported on spontaneous andor induced chromosome aberrations in cell cultures derived from male and female patients with DKC [Inoue et al, 1973;Morrison, 1974;Schroeder and Hofbauer, 1974;Sirinavin and Trowbridge, 1975;Burgdorf et al, 1977;Gutman et al, 1978;Carter et al, 1979;Connor and Teague, 1981;Kano and Fujiwara, 1982;Womer et al, 1983;Juneja et al, 1987;Aguilar-Martinez et al, 1988;Schneider et al, 1988;Scappaticci et al, 1989;Pai et al, 1989a,b;De Bauche et al, 1990;Kehrer et al, submitted]. The various forms of this disease may therefore belong to the group of precancerous syndromes characterized by chromosome instability.…”
Section: To the Editormentioning
confidence: 99%